KARAKTERISTIK CLEAT TERHADAP PERMEABILITAS DAN KANDUNGAN GAS PADA BATUBARA ANGGOTA M3 FORMASI MUARAENIM DI DAERAH MANGUNJAYA, PROVINSI SUMATRA SELATAN: CLEAT CHARACTERIZATION ON PERMEABILITY AND GAS CONTENT IN M3 MEMBERS OF MUARAENIM FORMATION AT MANGUNJAYA AREA, SOUTH SUMATRA PROVINCE - Ibrahim, Muhammad Abdurachman; Harianto, Tito (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2021)
South Sumatra Basin is the second largest resource of coal basin in Indonesia. The abundance of coal in this basin has opened up opportunities to exploring coal bed methane. Gas content and permeability affect the potential of coal bed methane in an area. Coal permeability is highly controlled by the cleat system that develops in the coal seam. Studies on cleat characterization in coal are mandatory to see the possible escape routes of methane gas in coal. This research was conducted to determine the relationship between the characteristics of coal, cleat system, and permeability. Coals from M3 of Muaraenim Formation were sampled for microcleat analysis. Coals from M3 is not to deep, having a good coal thickness, and one of the coal bed methane seams target, M3 members can be another coal bed methane target, besides M2 members which have proved to be coal bed methane target. Microcleat analysis was performed to observe face cleat, butt cleat, aperture and spacing. The correlation between permeability to gas content and depth of coal, illustrates that the greater permeability, the greater gas content.